TRANSITIONS TO FAMILY CAREGIVING OVER A 12-YEAR PERIOD IN THE NATIONAL REGARDS STUDY. (11th November 2018) - Roth, D; Rhodes, J; Sheehan, O; Huang, J; Jenny, N; Howard, V; Haley, W
Abstract: Most studies of family caregiving use convenience samples of persons who are already caregivers before enrollment. Population-based studies of those who prospectively transition into family caregiving roles are rare and needed. Participants in the REasons for Geographic and Racial Differences in Stroke (REGARDS) study were asked on two occasions if they were providing care to a family member or friend with a chronic illness or disability: at the REGARDS baseline telephone interview and at a 2nd interview 9–14 years later (M = 12 years). Those who transitioned into a significant caregiving role were recruited to participate in the Caregiving Transitions Study (CTS), which is examining health and serum biomarker responses to caregiving. Of 9, 863 REGARDS participants who were not caregivers at baseline, 1073 (11%) transitioned into a family caregiving role. Of these caregivers, 251 (23%) met eligibility criteria for the CTS and were enrolled along with 251 demographically-matched noncaregiving controls. Enrolled caregivers are 65% female; 36% African American; 69.1 + 7.8 years of age; caring for a spouse/partner (52%), parent (25%), or another person (23%); and 46% are caring for a person with dementia. Initial longitudinal comparisons reveal that depressive symptoms increased (d = 1.12 standard deviation units (SDUs), p < .0001) and health-related quality of life decreased (d = 0.35 SDUs, p < .0001) over the 12-year period for those who became caregivers. A unique sample of incident caregivers and matched controls has been assembled and analyses are currently examining changes on self-report and serum biomarker indicators of health.